On food and fodder: archaeobotanical investigations of Bamburgh Castle's west ward, 9th through 12th centuries - Blakeney, Rebecca A. (2017)
This dissertation details the identification, analysis and interpretation of archaeobotanical remains from nineteen contexts sampled from Bamburgh Castle’s West Ward. This study explores samples spanning the 8th through 13th centuries at the fortress. The interpretation of an early medieval grain-drying kiln is central to this report. The kiln is compared, both structurally and macrobotanically, to a selection of roughly contemporary kilns across Britain. This feature, and especially the charred plant remains preserved within, provide valuable evidence toward at least small-scale crop-processing activities at Bamburgh Castle during the Early Medieval period.